Emotionally responsive regulatory practices in FLL counseling and their evolving dynamics in interaction - Lazović, Milica (Frontiers in Communication, 2025)
In foreign language learning (FLL) advisory interactions, emotional responsiveness emerges as a central dimension, sustained through regulatory practices such as reappraisal, relabeling, self-disclosures, and simulated self-talk. Despite their importance, little is known about how novices without training in emotional regulation respond to learners' explicit negative emotional displays in contexts where emotions are backgrounded, generating tension in emotional reciprocity. This study examines the interactions of 28 pre-service teachers acting as FLL advisors for 28 international students in a service-learning context across two semesters. Data include audio recordings of 14 ad hoc advisory sessions and 14 seven-session counseling cycles, supplemented by team meetings. Using an interactional-linguistic approach, the study examines the linguistic resources that underlie emotional responsiveness and regulatory practices, focusing on their interplay and adaptive use across various interactions. Findings reveal a cluster of emotional-regulative practices along a continuum of increasing explicitness, complexity, and multidimensionality: emotional-regulative noticing, positive reorienting reappraisal in follow-up questions, emotionally supportive co-reasoning, transformative co-reasoning, postponed regulatory processing, extended meta-emotional episodes, and orchestrating multidimensional reappraisal in joint reasoning. All practices involve unpacking emotional displays into situated, narratively structured co-experiences, making them processable within the interactional interface of co-reasoning. Emotional responsiveness evolves dynamically across the counseling cycle, showing increased explicitness, functional recalibration, and argumentative integration, while context-dependent variations reflect advisors' adaptivity to the interactional history. The study highlights the need for systematic conceptualization of emotional responsiveness as a professional competency, providing a foundation for research on adaptive interpersonal regulation and emotionally responsive advising in FLL.